Penggunaan Forecasting dan Goal Programming dalam Optimasi Perencanaan Produksi Beras - Syifa Mardliyah; M. Yusuf Fajar; Farid H Badruzzaman (UNISBA Press, 2022)
Abstract. Rice is an important commodity in Indonesia because of its role as a staple food, which the majority of Indonesians consume every day as a carbohydrate intake. The “SM” Rice Shop is a place that manages rice production as well as sells it personally and to distributors. This shop produces 3 kinds of rice, namely white rice, brown rice, and white glutinous rice. The